EFFECTIVENESS AND MECHANISM OF PHYSICIAN HERBS FROM KALI PUTIH BATUR BANJARNEGARA CENTRAL JAVA AGAINST DIABETIC NEPHROPATHY - Kintoko, Kintoko; Witasari, Hardi Astuti; Wulan Kusumo, Djati; Kapri, Halid; Muldiyana, Tya; Wahyono, Slamet (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: Complications in the kidneys (nephropathy) are one of the chronic complications of diabetes mellitus (DM) most common microvascular and estimated to reach 30–40% of all sufferers of DM. Until now there is no cure drug that can prevent diabetic nephropathy. Therefore, the handling of this issue should be done seriously, one of them through an exploration of drug discovery and drug material. Ristoja in 2015 in the ethnic Javanese Banyumasan successfully explores the types of plants, herb, and traditional medicine culture. One is conducted by the Kaliputih Traditional Medicine, Batur, Banjarnegara, Central Java. Based on the results of the interview, traditional medicine has herb for disease therapy kidney failure which consists of 11 species of plants. Methods: The herbs were extracted by infundation method. Sprague Dawley albino male rats were divided into 3 groups (normal, positive, and negative) and 3 sample test groups with 3 different doses (18, 36, and 54 mL/kg body weight [BW]) previously induced streptozotocin. Observations were carried on the levels blood urea nitrogen (BUN), creatinine, uric acid, and nuclear factor kappa B (NF-κB), cyclooxygenase-2 (COX-2), and transforming growth factor-beta (TGF-β) kidney immunohistochemically and histology analysis. Results: Statistical results showed a significant increase of BUN levels in all dose variation groups after being given herbs, compared to the negative control group. The result of the examination of biochemical parameters of creatinine levels statistic showed significant (p<0.05) decrease in the dose 18 and 36 mL/kg BW compare with the negative group. The result of the study on histopathology kidney organs there are are damages to each test in each organ that is necrosis. The result of NF-κB, COX-2, and TGF-β expression no significant decrease compared with the negative controls. Conclusion: The herbs are not capable of nephropathy diabetic and need more research to know that activity as nephroprotective.